The chemical composition and antibacterial activity of essential oil from Minthostachys mollis (Orinoquia, 2016)
The chemical composition and antibacterial activity of essential oil from Minthostachys mollis were evaluated; the plants were grown in the Norte de Santander department, Colombia. The essential oil was obtained by conventional hydrodistillation from Minthostachys mollis leaves; relative density was determined at 20°C, as were the refraction index, essential oil solubility in ethanol (70% v/v) and optical rotation. Chemical composition was evaluated by gas chromatography/mass spectrometry (GC-MS). Three bacteria were used for evaluating antibacterial activity: Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 12228 and Escherichia coli ATCC 25922. The oil was diluted to the desired concentration (1,000-50 µg/mL) for determining antibacterial sensitivity and minimum inhibitory concentration, using the broth microdilution method, and a microplate reader was used for quantifying bacterial growth. Yield was 0.6%. Sensitivity test results revealed that bacteria were sensitive to essential oil from Minthostachys mollis; furthermore, this oil had a high content of oxygenated monoterpenes (i.e. carvacrol and thymol) having recognised antibacterial activity. It can thus be concluded that the vegetal species evaluated here is promising for controlling bacteria.Key words: Muña; essential oil; antibacterial activity.
Keywords: Muña; essential oil; antibacterial activity